Los instrumentos del nuevo orden mundial el derecho, la economía, la ciencia, el lenguaje y la religión en la sociedad del siglo XXI - Victoria Wilches, Pablo (Universidad Complutense de Madrid, Servicio de Publicaciones, 2008)
The main purpose of the present thesis is to present the social changes that have been recently taking place. The First Part examines the social phenomena fuelled by the emergence of what has been named the New Law. The Second Part analizes the ideological content of the economic models that are being taken as panaceas to cure all social ills, from the socialist conception to those of social justice and solidarity as alternatives to the capitalistic model. The Third Part examines from the philosophical perspective the "New Humanism" and its links to the religious and its downfall as a social alternative. The Third Part centers in society, science and the arts as instruments of a New World Order that is being imposed upon from the different strata of public life, including the United Nations and the non-governmental institutions that gravitate around it. All of these parts are being referenced as instruments employed for bringing about change and social reingeneering proposed by different international agencies and political movements, instruments that, such as semantics, sexual education, gender ideology and the legal definitions and roles assumed by the different Constitutional Courts that put forth sentences that are nowhere found in local legislation but nevertheless supersede it, are propellants of the new ideas that will eventually engulf the different world cultures.